INDIRUBIN-LOADED NANOLIPOSOMES MITIGATE DAUNORUBICIN- INDUCED CARDIOTOXICITY IN ALBINO WISTAR RATS: EVIDENCE FROM BIOCHEMICAL AND HISTOPATHOLOGICAL STUDIES (Applied Biological Research, 2025)
Daunorubicin, a widely used chemotherapeutic agent, is known for its potent anticancer effects but is severely limited by its dose-dependent cardiotoxicity. This study investigated the potential of indirubin-loaded nanoliposomes (INB-NLP) as a protective strategy to mitigate this cardiotoxicity in albino Wistar rats, supported by biochemical and histopathological evidence. The effects of INB-NLP on cardiac markers, lipid profiles, inflammatory markers, and enzymatic antioxidants were assessed by biochemical assays, ELISA, qRT-PCR, and histopathology using H&E staining.The study revealed a significant rise in cardiac troponin I (cTnI), total cholesterol, and triglyceride levels upon administration of daunorubicin (DNB). Post-treatment with INB-NLP significantly restored cTnI and lipid profiles to normal levels. DNB caused a marked reduction in SOD, CAT, and GST levels, which was significantly prevented by INB-NLP treatment. Diminished sirt3 expression in DNB-administered rats was restored by INB-NLP, while elevated caspase 8 (casp8) expression in the DNB group was significantly downregulated by INB-NLP treatment.Histopathological analysis of the aorta revealed severe damage in DNB-treated rats, including plaque formation, foam cell infiltration, and calcium deposition. INB-NLP treatment restored the aortic architecture. Overall, INB-NLP significantly prevented the oxidative damage caused by DNB, indicating its antioxidative and anti-inflammatory properties. These findings reveal the potential of INB-NLP as a cardioprotective agent by mitigating oxidative stress, inflammation, and tissue damage induced by DNB in rat myocardium.
Keywords: Daunorubicin; histopathology; indirubin; in vivo; nanoliposomes